2015
DOI: 10.1021/acs.biochem.5b00719
|View full text |Cite
|
Sign up to set email alerts
|

Ca2+ Interacts with Glu-22 of Aβ(1–42) and Phospholipid Bilayers to Accelerate the Aβ(1–42) Aggregation Below the Critical Micelle Concentration

Abstract: The amyloid cascade hypothesis links the amyloid-β (Aβ) peptide aggregation to neuronal cell damage and ultimately the etiology of Alzheimer's disease (AD). Although Aβ aggregation has been known to accelerate at cell membranes, the exact mechanism of Aβ peptide deposition and the involvement of extracellular species are still largely unclear. Using surface plasmon resonance (SPR) and atomic force microscopy (AFM), we demonstrate that Ca(2+) ions, in conjunction with lipid bilayer, lower the threshold concentr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 85 publications
2
12
0
Order By: Relevance
“…DLPC SLBs facilitate the rapid formation of globular aggregates on the bilayer surface of, and possibly within, the membrane. In contrast, most reports of membrane-mediated A␤ aggregation using AFM demonstrate the formation of conventional fibrils (41,47,48). This membrane-associated aggregation is probably responsible for the bilayer disruption, despite not occurring through the canonical amyloid formation pathway.…”
Section: Resultsmentioning
confidence: 81%
“…DLPC SLBs facilitate the rapid formation of globular aggregates on the bilayer surface of, and possibly within, the membrane. In contrast, most reports of membrane-mediated A␤ aggregation using AFM demonstrate the formation of conventional fibrils (41,47,48). This membrane-associated aggregation is probably responsible for the bilayer disruption, despite not occurring through the canonical amyloid formation pathway.…”
Section: Resultsmentioning
confidence: 81%
“…To confirm our simulation observation, we designed surface plasmon resonance (SPR) experiments to determine the Ca 2+ effect on the adsorption of Aβ peptides onto lipid bilayers . SPR results clearly showed that in the presence of Ca 2+ , Aβ 1–42 peptides adsorbed on a supported DPPS bilayer are 9‐fold higher than those in the absence of Ca 2+ (Figure ).…”
Section: Amyloid‐membrane Interactions Linked To Amyloid Toxicitymentioning
confidence: 60%
“…The expected conformational transition is well documented, cf. Fig 22A(a) and 22A(b) [ 176 , 177 , 181 184 ], and may well contribute to the catalysis of polymerization by membranes and lipid rafts [ 247 254 ].…”
Section: Resultsmentioning
confidence: 99%
“…The expected conformational transition is well documented, cf. Fig 22A(a) and 22A(b) [ 176 , 177 , 181 184 ], and may well contribute to the catalysis of polymerization by membranes and lipid rafts [ 247 254 ]. (D) (a) The ( S )-cysteine can bring together two Aβ molecules via three-point binding of Asp-1, in spite of a degree of steric strain in either chelation mode; (b) The ( R )-cysteine can tightly bind one Aβ molecule in a complex free of strain, but bringing in the second Aβ molecule is impossible due to prohibitive steric hindrance; (c) Thus, the ( S )-cysteine would promote formation and release of the Aβ↑Aβ↓ dimer and therefore accelerate polymerization (the blue curve in the insert), while the ( R )-cysteine would immobilize isolated Aβ molecules on the graphene surface and therefore slow down polymerization (the red curve in the insert).…”
Section: Resultsmentioning
confidence: 99%